2013
DOI: 10.1667/rr3196.1
|View full text |Cite
|
Sign up to set email alerts
|

Biological Dosimetry by Automated Dicentric Scoring in a Simulated Emergency

Abstract: Dicentric chromosome analysis remains the most widely used method in biodosimetry. It has a lower detection limit of about 0.1 Gy, and allows one to distinguish between whole- and partial-body exposures. A drawback of the dicentric analysis is that it is a time consuming method and maybe difficult to implement in a mass casualty event. To try to increase the analysis capacity, automatic dicentric scoring (ADS) using image analysis software is being incorporated in several laboratories. Here we present the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…The validation of the automated image analysis systems, particularly chromosomeaberration image analysis systems, must address the number of false-positives and false negatives per comparison to the expert manual scoring of the same spreads. The outcomes of the studies of Vaurijoux et al [15] and of Gruel et al [16] show that this technique is reproducible when workflow employs QA&QC process. Further, examination of all the methodological parameters is necessary, if any changes are desired to an already established method during a technical validation.…”
Section: Figmentioning
confidence: 94%
“…The validation of the automated image analysis systems, particularly chromosomeaberration image analysis systems, must address the number of false-positives and false negatives per comparison to the expert manual scoring of the same spreads. The outcomes of the studies of Vaurijoux et al [15] and of Gruel et al [16] show that this technique is reproducible when workflow employs QA&QC process. Further, examination of all the methodological parameters is necessary, if any changes are desired to an already established method during a technical validation.…”
Section: Figmentioning
confidence: 94%
“…In the case of radiation biodosimetry, an estimated 50,000 individuals will need to be evaluated within 2 to 6 days after a 10 kt bomb, according to military scenarios for planning (Flood et al, 2016a), although in a city such as New York, NY or Washington, DC the number may well be much higher. Complete blood count (CBC) differential for lymphocyte depletion kinetics, premature chromosome condensation (PCC), dicentric measurement, gene expression, γ-H2AX, cytokinesis block micronucleus assay (CBMN), protein biomarkers, metabolic biomarkers, and electron paramagnetic resonance (EPR) or optically stimulated luminescence (OSL) of teeth have been proposed as some of the methods for radiation biodosimetry (Amundson and Fornace, 2003, Brengues et al, 2010, Coy et al, 2011, Gruel et al, 2013, Lamadrid Boada et al, 2013, Sharma and Moulder, 2013, Sullivan et al, 2013, Xu et al, 2013, Hu et al, 2015, Flood et al, 2016b, Garty et al, 2016, Sproull and Camphausen, 2016). However, some of these assays require a significant length of time for processing and highly trained personnel to perform the assays and interpret the results.…”
Section: Introductionmentioning
confidence: 99%
“…Romm et al 2013;Vaurijoux et al 2015). Indeed, Gruel and colleagues demonstrated that semi-automated analysis can also be used in emergency response, with dose estimates based on as few as 50 cells (Gruel et al 2013). The dicentric assay is still recognised as the international gold-standard method for biological dosimetry and classification of genotoxic agents.…”
Section: The Aims Of This Inter-comparison Werementioning
confidence: 99%